2019
DOI: 10.1016/j.psychres.2019.112625
|View full text |Cite
|
Sign up to set email alerts
|

The importance of loneliness in psychotic-like symptoms: Data from three studies

Abstract: Poor social connection or loneliness is a prominent feature of schizotypy and may exacerbate psychosis risk. Previous studies have examined the interrelationships between loneliness and psychosis risk, but critically, they have largely been conducted in non-clinical samples or exclusively used laboratory questionnaires with limited consideration of the heterogeneity within schizotypy (i.e., positive, negative, disorganized factors). The present study examined links between loneliness and psychotic-like symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 72 publications
(92 reference statements)
2
20
0
Order By: Relevance
“…Undergraduate students who endorsed more schizotypal items also reported more loneliness in their day-to-day lives. This is consistent with previous research indicating that loneliness is related to psychotic-like experiences and is a risk factor for the development of psychotic disorders [ 19 , 20 ]. Additionally, this finding might have important implications for interventions on loneliness with individuals who might be at risk for psychosis [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Undergraduate students who endorsed more schizotypal items also reported more loneliness in their day-to-day lives. This is consistent with previous research indicating that loneliness is related to psychotic-like experiences and is a risk factor for the development of psychotic disorders [ 19 , 20 ]. Additionally, this finding might have important implications for interventions on loneliness with individuals who might be at risk for psychosis [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…The association between loneliness and hallucinations has been demonstrated across several different disorders including borderline personality disorder [ 17 ], Alzheimer’s disease [ 18 ], and psychosis [ 19 ]. Additionally, in the presence of loneliness, psychotic-like symptoms increased for individuals with high levels of negative and disorganized schizotypal traits [ 20 ]. This finding supports the argument that the context of loneliness might increase the likelihood of psychotic-like experiences in already vulnerable individuals.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we found that schizotypy scores stayed the same or even increased, which is highly interesting, considering that already during the first timepoint nearly 10% of the responders indicated a subjective increase of symptoms. Recent work shows the impact of adverse life events or loneliness on developing psychotic-like experiences (Beards et al, 2013; Chau et al, 2019; Le et al, 2019; Betz et al, 2020). The social and life-changing consequences of this pandemic (i.e., general reduction of social interaction, job insecurity, experiencing health problems) might therefore provide a long-term risk in those individuals with high schizotypy scores.…”
Section: Discussionmentioning
confidence: 99%
“…This might have been expected that with the continuing course of the pandemic, social isolation might increase, and with that, potentially loneliness too. Loneliness significantly interacts with schizotypy, and has been clinically linked to risk-for psychosis (Chau et al, 2019; Le et al, 2019). Again, this finding is of great clinical relevance and furthermore requires the attention of decision makers in a situation like the current.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a recent review by Preti et al (2020) the current pandemic poses an especially large risk for people suffering from paranoid or high schizotypal traits, as the measures taken to prevent the spread of the virus might ultimately lead to increased anxiety and depressive symptoms, increased avoidance behaviors, stronger disruption of social contacts, and delayed return to normality in these individuals. Furthermore, studies show links between recent adverse life events ( Beards et al, 2013 ; Betz et al, 2020 ) or isolation and loneliness ( Chau et al, 2019 ; Le et al, 2019 ) and schizotypy or psychosis-like experiences. Both these aspects, loneliness and adverse life events, are present in the current pandemic, which might have a worsening effect on schizotypal trait expression in people with pre-existing high schizotypy scores, perhaps leading to increased distress or disability.…”
Section: Introductionmentioning
confidence: 99%